The Coagulability of Partially Lysed Fibrinogen Effect of pH and Ionic Strength - Triantaphyllopoulos, D. C; Torres, Mary (Thrombosis and Haemostasis, 1971)
Addition of thrombin to plasma obtained from dogs injected with plasmin clotted more fibrinogen when the plasma was diluted with saline than when it was diluted with distilled water. In contrast, more fibrin was formed in dilutions with distilled water when thrombin was added to intact plasma obtained prior to the injection of plasmin.The same phenomenon was observed with purified human fibrinogen submitted to limited digestion with plasmin and was found to be pH dependent. When the pH was greater than 7.3 more fibrin was formed if the fibrinogen was diluted with saline than if it was diluted with distilled water. The opposite was observed at pH values lower than 7.2.Similar results were obtained with the fraction of partially lysed human fibrinogen which precipitates at 25% saturation with ammonium sulfate. The same fraction, however, obtained from partially digested bovine fibrinogen did not react exactly the same way. In dilutions with distilled water there was an inverse relationship between the pH value and the amount of protein which clotted; but the reverse did not apply to the same extent in dilutions with saline.At variance to the above observations the clottability of purified intact fibrinogen was not significantly altered by changes in pH or in ionic strength.The clottability of partially lysed human plasma could be reversed (more fibrin in distilled water than in saline) after exhaustive dialysis against oxalated (pH 7.0) but not against citrated (pH 7.8) saline indicating that the change in clottability was due to a change in pH.